2011
DOI: 10.1088/0960-1317/21/4/043001
|View full text |Cite
|
Sign up to set email alerts
|

A review of micro-powder injection moulding as a microfabrication technique

Abstract: Micro-powder injection moulding (μPIM) is a fast-developing micro-manufacturing technique for the production of metal and ceramic components. Shape complexity, dimensional accuracy, replication fidelity, material variety combined with high-volume capabilities are some of the key advantages of the technology. This paper assesses the capabilities and limitations of μPIM as a micromanufacturing technique by reviewing the latest developments in the area and by considering potential improvements. The basic elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 116 publications
(494 reference statements)
0
69
0
1
Order By: Relevance
“…Among the micro-manufacturing technologies, Micro Powder Injection Moulding (μPIM) [3] is capable of manufacturing metallic and ceramic micro-components and systems of complex shapes with very good dimensional accuracy combined with high volume capability. μPIM is an extension and miniaturized version of PIM…”
Section: Micro Powder Injection Mouldingmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the micro-manufacturing technologies, Micro Powder Injection Moulding (μPIM) [3] is capable of manufacturing metallic and ceramic micro-components and systems of complex shapes with very good dimensional accuracy combined with high volume capability. μPIM is an extension and miniaturized version of PIM…”
Section: Micro Powder Injection Mouldingmentioning
confidence: 99%
“…It has been shown that metallic powders in the semisolid state can be successfully used to fabricate a two layer functionally graded structure with one layer of aluminium-siliconcopper alloy and the other layer being SiC particles reinforced alloy. Figure 6 shows a schematic of semisolid powder processing set up [3]. …”
Section: Semi Solid Powder Processing (Sspp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the number of applications and the interest in the technology, the demand for reliable simulation tools increases [1,2]. In (powder) injection molding, simulations are a very useful tool to accompany and support the design process of the actual part as well as of the mold and the process.…”
Section: Introductionmentioning
confidence: 99%
“…As remarked by Heaney (2012) and many other authors, this promising technology has experienced rapid growth due to the rising demand for the application of micro components. Attia and Alcock (2011) compiled a thorough revision of PIM. Micro components are classified into the three categories, namely: micro parts, microstructured components and micro-precision parts.…”
Section: Introductionmentioning
confidence: 99%